Antischistosomal Activity of Oxindolimine-Metal Complexes - de Moraes, Josué (Antimicrob Agents Chemother, 2015)
In recent years, a class of oxindole-copper and -zinc complex derivatives have been reported as compounds with efficient proapoptotic activity toward different tumor cells (e.g., neuroblastomas, melanomas, monocytes). Here we assessed the efficacy of synthesized oxindole-copper(II), -zinc(II), and -vanadyl (VO(2+)) complexes against adult Schistosoma mansoni worms. The copper(II) complexes (50% inhibitory concentrations of 30 to 45 μM) demonstrated greater antischistosomal properties than the analogous zinc and vanadyl complexes regarding lethality, reduction of motor activity, and oviposition.